1992
DOI: 10.1016/0014-5793(92)80580-a
|View full text |Cite
|
Sign up to set email alerts
|

d‐Glyceraldehyde‐3‐phosphate dehydrogenase purified from rabbit muscle contains phosphotyrosine

Abstract: Homogeneous preparations of D-glyceraldehydc.3-phosphate dehydrogenase purified from rabbit muscle were found to contain 0,2-0,7 moles of covalently bound phosphate per mole of the enzyme. With the use of anti-phospholyrosine antibodies, evidence was obtained that the enzyme is phosphorylated at tyrosine residues.o-Glyeeraldehyde-3-phosphate dehydrogenase; Endogenous phosphate; Phosphotyrosine; Antibody to phosphotyrosine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
(4 reference statements)
1
13
0
1
Order By: Relevance
“…The exact GAPDH amino acid modified by these kinases is unknown; however, preliminary studies suggest a Tyr as the site of phosphorylation [13, 98]. Furthermore, studies have shown that mammalian, tetrameric GAPDH was auto-phosphorylated in the presence of ATP and Mg 2+ in a concentration-dependent manner and dephosphorylated in the presence of NAD + , NADH, and/or G3P [9, 14, 15].…”
Section: 0 Gapdh Functional Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…The exact GAPDH amino acid modified by these kinases is unknown; however, preliminary studies suggest a Tyr as the site of phosphorylation [13, 98]. Furthermore, studies have shown that mammalian, tetrameric GAPDH was auto-phosphorylated in the presence of ATP and Mg 2+ in a concentration-dependent manner and dephosphorylated in the presence of NAD + , NADH, and/or G3P [9, 14, 15].…”
Section: 0 Gapdh Functional Diversitymentioning
confidence: 99%
“…A second way GAPDH is involved in apoptosis is through post-translational modification and small molecule/protein interactions, including Ap4A binding [5, 124], VDAC-1 binding [99], phosphorylation [8–15, 98], S -glutathionylation (Section 5.1.1), p53 binding (Section 5.1.2), S -nitrosylation (Section 5.1.3), and AβPP binding (Section 5.4). Ap4A is a part of the diadenosine oligophosphate (ApnA) signal-transduction family of molecules, which play a role in DNA replication and repair through binding cell membranes and the DNA polymerase-α complex [5, 95, 124].…”
Section: 0 Gapdh and Alzheimer Diseasementioning
confidence: 99%
“…For Western blotting for GLUT1, GLUT4, or PPARg, cells were treated for 72 h with FGF-21 (50 nM), rosiglitazone (1 mM), or both. Cell lysates were immunoblotted with anti-GLUT1 against the 29 C-terminal amino acids of the human sequence, anti-GLUT4 (Slieker et al, 1992), anti-PPARg (Santa Cruz) or anti-GAPDH (Sergienko et al, 1992). PPARg protein bands were quantitated from film using a Molecular Dynamics Personal Densitometer SI with ImageQuant TM software (GE Healthcare, Piscataway, NJ).…”
Section: Cell Culturementioning
confidence: 99%
“…These include its role in nuclear RNA transport (42), modulation of cytoskeletal structure (43), DNA repair (44), and apoptosis (45). We observed, in this study, that an increase in GAPDH protein levels in PLC-γ l-transformed cells was significantly correlated with ATP production and anchorage-independent growth ( Figure 6).…”
Section: Discussionmentioning
confidence: 47%